Validasi Video Dokumenter PJES (Penjajahan Jepang Memantik Empati Sejarah) Siswa - Rizki, Latifah; Aisiah, Aisiah (YASIN, 2025)
History learning media at SMAN 5 Pariaman remains dominated by conventional tools that are less effective in fostering students’ historical empathy. In contrast, innovative media such as documentary videos have the potential to help students internalize and emotionally connect with the suffering experienced by Indonesians during the Japanese occupation (1942–1945). This study aims to assess the feasibility, practicality, and effectiveness of a documentary video titled PJES (Penjajahan Jepang Membangun Empati Sejarah), developed to cultivate historical empathy among high school students. A quantitative approach was employed, involving 36 participants, including content validators, media validators, a history teacher, and students. Data were collected through feasibility, practicality, and effectiveness tests using Likert-scale validation sheets and analyzed using mean score formulas. The results showed that: (1) the documentary content was rated highly feasible, with an average content validator score of 3.6; (2) media quality was also rated highly feasible, with a mean score of 3.6 from media validators; (3) the level of practicality was rated very practical, with teacher and student scores of 3.8 and 3.5 respectively; (4) media effectiveness was rated very effective, with mean scores of 3.7 (teacher) and 3.5 (students). The study concludes that the PJES documentary video is feasible, practical, and effective for use in history education to foster historical empathy regarding the Japanese occupation. The findings imply that the development of similar media can serve as a meaningful and emotionally engaging alternative in history learning.